COMEDY OF IDEAS: STUDY OF OZICK’S BLOODSHED AND THREE NOVELLAS - Parmar, Shipra; Sood, Dr Reetika (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Cynthia Ozick is an emphatic voice of new Jewish American novels who reveals various issues that a Jew has to face while living in a mainstream American culture. She advocates ethnicity and chooses the comic mode to reveal the truth. The present paper aims at the in-depth study of the second collection of short stories "Bloodshed and three Novellas’. In these stories Ozick which focuses on the betrayal of tradition by Jews. She brings out the hilarious situations and ideas by focusing on various flaws and blemishes in the personalities of her characters. She also mocks at their defective physical appearances. In fact the comic elements in her fiction have a much higher purpose than only evoking laughter. The present paper also attempts to study how Ozick’s comedy is a mirror of human reality and focuses on humanity. The present paper is an endeavour to show how Ozick’s comedy has a fair share of flippancy, folly and jest and how it manifests itself in forms like irony, satire, grotesque and farce.